Multiconfigurational Dirac-Fock Energy Levels and Radiative Rates for Kr XX (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2017)
In present calculations, energy levels and radiative properties are reported for transitions in Cl-like Kr. For these calculations, the fully relativistic multiconfigurational Dirac-Fock (MCDF) approach is employed by including 54 configurations (generating 5370 levels) and the Breit and quantum electrodynamics effects. To assess the accuracy of presented results, calculations have also been performed for energy levels using the fully relativistic flexible atomic code (FAC) and comparisons are made with the existing experimental and theoretical data. Energies are reported for the lowest 100 levels corresponding to the configurations 3s23p5, 3s3p6, 3s23p43d, 3s3p53d, 3s23p33d2 and radiative rates are provided for E1 and M2 transitions from ground state.
Keywords: Atomic data; Cl-like Kr; Multiconfigurational Dirac-Fock method